The role of bacterial superantigens in skin diseases - Barańska-Rybak, Wioletta; Sokołowska-Wojdyło, Małgorzata; Trzeciak, Magdalena; Michajłowski, Igor; Maciejewska-Radomska, Agata; Nowicki, Roman; Roszkiewicz, Jadwiga (Dermatology Review/Przegląd Dermatologiczny, 2009)
Superantigens are high-molecular-weight proteins comprising a group of molecules produced by various microorganisms. They are involved in pathogenesis of several human diseases (atopic eczema, toxic shock syndrome, psoriasis, Kawasaki disease). In contrast to conventional antigens, superantigens bypass intracellular processing and bind directly to the major histocompatibility complex (MHC) class II molecule, on the surface of the antigen processing cell, outside the antigen-binding groove. Superantigens are characterized by their capacity to stimulate a large number of T-cells. The superantigen then cross-links the MHC class II molecule on the antigen presenting cell with T-cells according to the composition of the variable region of the T-cell receptor Vb chain, leading to polyclonal T-cell activation and cytokine release. We present the current knowledge concerning the role of staphylococcal and streptococcal superantigens in some skin diseases.